Conceptual Design of Vertical Passenger Seat for Standing Cabin in Commercial Transport Aircraft. - Romli, Fairuz Izzudin; Mohamad Noor, Ahmad Redzman (2013)
The competition between airlines today is changed towards the affordability of their air transportation service. The airlines are competing to lower their offered flight ticket prices as to capture high demands from leisure and business travelers, who are also price-sensitive customers. Theoretically, by having more passengers onboard the aircraft, the flight ticket price can be lowered since the imposed operational costs can be shared by more passengers per flight. The standing cabin concept has been proposed where the passengers are transported in a cabin of an aircraft in an upright position, similar to standing on buses and trains. This paper explores the conceptual design of vertical seat for the passengers to be applied in such standing cabin concept.